Determination of dynamic amplification factors for heavy haul railways. (February 2018) - Zhao, Xin; Yang, Jizhong; An, Boyang; Liu, Chao; Cao, Yabo; Wen, Zefeng; Jin, Xuesong
A new approach has been developed to determine the dynamic amplification factors of railways. This approach employs a traditional multi-body dynamic model of vehicle–track interaction and a 3D explicit finite element model of wheel–rail rolling contact to treat the low- and high-frequency dynamics, respectively. Excitations are considered by contact surface unevenness and more specifically, by the power spectrum density of track irregularity for the low-frequency analysis and by the critical wheel flat, weld, and rail corrugation for the high frequency. For the 40-tonne axle load heavy haul railway simulated in this work, it has been found that the optimum fastening stiffness should be 150–200 MN/m; the dynamic amplification factors of the wheel–rail contact, fastening, and ballast forces are 1.94, 2.0, and 1.67, respectively, if the fastening stiffness of 200 MN/m is applied. Finally, new dynamic amplification factor formulae that include key parameters such as the fastening stiffness, speed, and axle load are proposed for the heavy haul railway design.